Ragam Pendidikan Guru Masa Pemerintahan Kolonial Hindia Belanda - Kurniawati, Yeni; Santosa, Ayi Budi (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
This article aims to describe the pattern of teacher education during the Dutch Colonial period, which was adapted to the colonial education system. This research uses historical methods with heuristic steps (source search), source verification (internal and external criticism), interpretation, and historiography. The sources used are archives from ANRI (National Archives of the Republic of Indonesia), the KTLV Library, and the National Library. Apart from that, the primary source used is Algemeen Verslag van het Inlandsch Onderwijs in Nederlandsch-Indiё Loopende over de Jaren 1893 t/m 4. At the beginning of the 20th century, the Dutch East Indies government established many schools that needed skilled teaching staff. Kweekschool was founded to meet the needs of native teachers for existing schools at that time. Apart from teacher education called kweekschool, there are also other teacher schools such as Hogere Kweekschool (HKS), Hollands Inlandsche Kweekschool (HIK), Hollands Chinese Kweekschool (HCK), and Hoofdakte Course. In 1907, the teacher education program was extended from four to six years, and the Dutch began establishing advanced teacher schools, Hoogere Kweekschool (HKS) in 1914 in Bandung and Purworejo.